A NOTE ON THE FISHERY OF THE NORTH INDIAN FRESHWATER PRAWN, MACROBRACHWM BIRMANICUM CHOPRAI, IN THE MIDDLE STRETCH OF RIVER GANGA - Prakash, Shree; Agarwal, G P (Indian Journal of Fisheries, 2011)
The indices in variability of catch and the relative abundance of Macrohrtichhim hirmanicam choprai show three distinct seasons in landing pattern, with relatively unimportant cyclical movements. Gradual decline of fisheries from year to year, increase in bulk from upper to lower centres and direct co-relation with rainfall have been observed.